2017
DOI: 10.12659/msm.902637
|View full text |Cite
|
Sign up to set email alerts
|

Role of Circulating Tumor Cell (CTC) Monitoring in Evaluating Prognosis of Triple-Negative Breast Cancer Patients in China

Abstract: BackgroundBreast cancer (BC) is the most common malignant tumor in females. This study investigated the role and utility of CTC monitoring in evaluating the prognosis of triple-negative breast cancer patients.Material/MethodsWe enrolled 286 female triple-negative breast cancer patients who were diagnosed at and received radical resection surgery in our hospital. Peripheral venous blood samples were collected preoperatively and at 3 and 7 days postoperative, and the Cell Search system was used to detect CTC in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 38 publications
2
21
0
Order By: Relevance
“…The percentage of CTC detection described in other studies varies between 16% and 73% depending on the analytic methods used and the tumor stage [5,7]. Thus, for example, Zhang et al analyzed the levels of peri-operative CTCs using CellSearch technology in 286 cases of stages I, II and III TNBC, finding CTCs in the 23%, 37% and 56%, respectively, for each stage [7]. In a cohort of 102 patients with stage IV TNBC, Magbanua et al described a detection rate (CTCs ≥5) with the CellSearch system before starting chemotherapy of 44%, and 15 days after starting treatment this percentage dropped to the 33%.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The percentage of CTC detection described in other studies varies between 16% and 73% depending on the analytic methods used and the tumor stage [5,7]. Thus, for example, Zhang et al analyzed the levels of peri-operative CTCs using CellSearch technology in 286 cases of stages I, II and III TNBC, finding CTCs in the 23%, 37% and 56%, respectively, for each stage [7]. In a cohort of 102 patients with stage IV TNBC, Magbanua et al described a detection rate (CTCs ≥5) with the CellSearch system before starting chemotherapy of 44%, and 15 days after starting treatment this percentage dropped to the 33%.…”
Section: Discussionmentioning
confidence: 97%
“…Importantly, 42% of all analyzed patients were positive for CTCs (at least 1 CTCs) using CellSearch system, with all the positive cases being of metastatic patients. The percentage of CTC detection described in other studies varies between 16% and 73% depending on the analytic methods used and the tumor stage [5,7]. Thus, for example, Zhang et al analyzed the levels of peri-operative CTCs using CellSearch technology in 286 cases of stages I, II and III TNBC, finding CTCs in the 23%, 37% and 56%, respectively, for each stage [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence suggests that poor prognosis in breast cancer might relate to CTCs [13,14], and the survival of tumor cells in circulation requires three aspects: 1.resistance to anoikis, 2. escape immune surveillance, and 3. being stable under blood shearing force. The resistance to anoikis requires several signaling pathways related to anchorage-independent growth and epithelial-mesenchymal transition, including Akt, TrkB, Src, and so on [15].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, numerous researches have demonstrated that CTC analysis could be used in detecting early tumor progression of various kinds of cancer, including breast, colorectal, prostate cancers and so on. [4][5][6][7] Thus, CTC analysis is now regarded as "liquid biopsy" and has been used in clinical application to predict the clinical outcomes and monitor treatment responses throughout the course of diseases. Although Cell Search™ had been allowed by the US Food and Drug Administration to detect CTCs in the clinical application in 2004, it was still constrained by its low sensitivity in epithelial cell adhesion molecule (EpCAM)-negative cases.…”
Section: Introductionmentioning
confidence: 99%